Liraglutide Ameliorates Erectile Dysfunction via Regulating Oxidative Stress, the RhoA/ROCK Pathway and Autophagy in Diabetes Mellitus - Yuan, Penghui; Ma, Delin; Gao, Xintao; Wang, Jiaxing; Li, Rui; Liu, Zhuo; Wang, Tao; Wang, Shaogang; Liu, Jihong; Liu, Xiaming (Frontiers in Pharmacology, 2020)
Background Erectile dysfunction (ED) occurs more frequently and causes a worse response to the first-line therapies in diabetics compared with non-diabetic men. Corpus cavernosum vascular dysfunction plays a pivotal role in the occurrence of diabetes mellitus ED (DMED). The aim of this study was to investigate the protective effects of glucagon-like peptide-1 (GLP-1) analog liraglutide on ED and explore the underlying mechanisms in vivo and vitro. Methods Type 1 diabetes was induced in rats by streptozotocin, and the apomorphine test was for screening the DMED model in diabetic rats. Then they were randomly treated with subcutaneous injections of liraglutide (0.3 mg/kg/12h) for 4 weeks. Erectile function was assessed by cavernous nerve electrostimulation. The corpus cavernosum was used for further study. In vitro, effects of liraglutide were evaluated by primary corpus cavernosum smooth muscle cells (CCSMCs) exposed to low or high glucose (HG)-containing medium with or without liraglutide and GLP-1 receptor (GLP-1R) inhibitor. Western blotting, fluorescent probe, immunohistochemistry and relevant assay kits were performed to measure the levels of target proteins. Results Administration of liraglutide did not significantly affect plasma glucose and body weights in diabetic rats, but improved erectile function, reduced levels of NADPH oxidases and ROS production, downregulated expression of Ras homolog gene family (RhoA) and Rho-associated protein kinase (ROCK) 2 in the DMED group dramatically. The liraglutide treatment promoted autophagy further and restored expression of GLP-1R in the DMED group. Besides, cultured CCSMCs with liraglutide exhibited a lower level of oxidative stress accompanied by inhibition of the RhoA/ROCK pathway and a higher level of autophagy compared with HG treatment. These beneficial effects of liraglutide effectively reversed by GLP-1R inhibitor. Conclusion Liraglutide exerts protective effects on ED associated with the regulation of smooth muscle dysfunction, oxidative stress and autophagy, independently of a glucose- lowering effect. It provides new insight into the extrapancreatic actions of liraglutide and preclinical evidence for a potential treatment for DMED.